Daytime sleepiness in Parkinson's disease: a multifaceted symptom - Di Laudo, Felice; Baldelli, Luca; Mainieri, Greta; Loddo, Giuseppe; Montini, Angelica; Pazzaglia, Caterina; Sala, Monica; Mignani, Francesco; Provini, Federica (Frontiers in Sleep, 2023)
Excessive daytime sleepiness is a symptom experienced by more than one-third of patients with Parkinson’s Disease and ism associated with disease duration and severity, dopaminergic therapy, and several non-motor symptoms. In recent years, growing evidence has been suggesting “primary” sleepiness in Parkinson, due to common pathophysiological features: for this reason, it is crucial to recognize sleepiness in these patients, investigate and exclude other conditions possibly leading to sleepiness (e.g., heavy dopaminergic therapy or breathing disorders during sleep). For both in- and out-patients, the key to a correct diagnosis is a structured clinical interview, together with questionnaires for better symptoms’ characterization and the use of objective measures as the most precise method to assess excessive daytime sleepiness. Finally, there are some therapeutical approaches that may be attempted for these patients and, although there is still no consensus on a standardized therapy, clinical trials with new drugs are currently on the go.